2012
DOI: 10.2298/abs1201297m
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drought on the expression of TAO1, NCED and EIL1 genes and ABA content in tomato wild-type and flacca mutant

Abstract: The effects of drought (partial root-zone drying-PRD and regulated deficit irrigation-RDI) and full irrigation (FI) on the expression of ABA biosynthetic genes (TAO1 and NCED), EIL1 gene and ABA content in the leaves of tomato wild-type (WT) and flacca mutant were investigated. Results confirmed differences in the expression of the investigated genes under the investigated treatments, during treatment duration as well as between investigated WT and flacca plants. The most significant differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Our result on the up-regulation of the NCED1 gene under water deprivation is in line with the observed ABA accumulation in tomato leaves (Figure 6). The up-regulation of NCEDs genes under drought has been demonstrated elsewhere [61,62,65,66]. We assume that the more pronounced expression of the NCED1 gene in WT observed in the 3rd drought cycle was mostly due to its de novo biosynthesis, while in the 1st and 2nd cycles the ABA was synthesized from its precursors and conjugates.…”
Section: Low Aba Differences Results In Flacca Traitsmentioning
confidence: 68%
“…Our result on the up-regulation of the NCED1 gene under water deprivation is in line with the observed ABA accumulation in tomato leaves (Figure 6). The up-regulation of NCEDs genes under drought has been demonstrated elsewhere [61,62,65,66]. We assume that the more pronounced expression of the NCED1 gene in WT observed in the 3rd drought cycle was mostly due to its de novo biosynthesis, while in the 1st and 2nd cycles the ABA was synthesized from its precursors and conjugates.…”
Section: Low Aba Differences Results In Flacca Traitsmentioning
confidence: 68%
“…Our results showed that drought-induced accumulation of ABA in the leaves was more pronounced in wild type compared to flacca mutant (Table 4) that could be explained a specific stomata and leaf response. Investigation of gene expression in Ailsa Craig leaves indicate a synergistic effect of signaling pathways for ABA and ethylene, while in flacca the expression of the NCED gene was reduced and EIL1 was increased, which indirectly imply an increase in the concentration of ethylene [30]. Therefore, the explanation for the smaller leaf area and mass of flacca mutant or specific leaf response compared to the wild type may be due to decreased ABA production or increased ethylene concentration.…”
Section: Biochemical and Metabolic Processesmentioning
confidence: 99%
“…Tomato (Solanum lycopersicum) plants exposed to DI and PRD showed no consistent changes in the expression of genes related to ABA biosynthesis (SlTAO1 and SlNCED) and ethylene sensitivity (SlEIL1; [18]), and these changes were not consistently related to soil or plant water status.…”
Section: Introductionmentioning
confidence: 99%